Proceedings of the 2nd ACM Workshop on Cyber-Physical Systems Security and Privacy 2016
DOI: 10.1145/2994487.2994489
|View full text |Cite
|
Sign up to set email alerts
|

Towards Safe and Secure Autonomous and Cooperative Vehicle Ecosystems

Abstract: Semi-autonomous driver assists are already widely deployed and fully autonomous cars are progressively leaving the realm of laboratories. This evolution coexists with a progressive connectivity and cooperation, creating important safety and security challenges, the latter ranging from casual hackers to highly-skilled attackers, requiring a holistic analysis, under the perspective of fully-fledged ecosystems of autonomous and cooperative vehicles. This position paper attempts at contributing to a better underst… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
26
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(27 citation statements)
references
References 51 publications
1
26
0
Order By: Relevance
“…Since software ecosystems involves governmental rules, relevant white papers were also identified. The identified literature body is gathered in Section 5, numbered from [18][19][20][21][22][23][24][25][26][27][28][29]…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Since software ecosystems involves governmental rules, relevant white papers were also identified. The identified literature body is gathered in Section 5, numbered from [18][19][20][21][22][23][24][25][26][27][28][29]…”
Section: Methodsmentioning
confidence: 99%
“…In [27] Semi-autonomous and fully autonomous cars are described as coming from the development stage to actual operations. The autonomous systems are creating safety and security challenges.…”
Section: Risk Governance Of Smart Cities (Software Ecosystems) -Vulnementioning
confidence: 99%
“…In fact, the concepts of dependability and security are closely related [2] and in some cases, the proposed solutions aim to increase both the dependability and security attributes of the network. Nevertheless, an effort was made on this survey to avoid the analysis of strategies focusing on the security issues of vehicular communications, since this could be the topic of another review paper, given the large number of threats already identified in the literature [3]. In addition, the search was limited to fault-tolerant techniques specifically addressing vehicular network issues, not broader research topics such as mobile ad-hoc networks (MANETs), or similar fields e.g., mobile sensor networks (MSNs).…”
Section: Introductionmentioning
confidence: 99%
“…1, the architecture we propose enables Fast Failover [1] in the case of a link failure and message delivery in a timely manner regardless of data frequency or refresh rate, this will solve the lack of failover support by LIVNs. Our design has also the added benefit of leveraging unicast communications instead of broadcasts, reducing the risk of eavesdropping on automotive components [12]. Our contribution features SDN as an overlay on top of the CAN bus and the other LIVNs.…”
Section: Introduction and Related Workmentioning
confidence: 99%